PENERAPAN ASPEK RITMIS DALAM MEMBANGUN FILM “EGO” DENGAN GENRE DRAMA KOMEDI - I Made Angga Wicaksana Yasa; Ni Kadek Dwiyani; I Made Denny Chrisna Putra (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
The editing aspect is a technique that is well known in the film world, especially editing. At the beginning of the development of film, filmmakers were well aware of the powerful influence of the editing aspect in manipulating time and space. Editors can choose one of the four aspects of editing, one of which is the rhythmic aspect which will be applied to the making of a film entitled "Ego". This writing will examine how the application of the rhythmic aspects to each scene and how the rhythmic aspects can influence the narrative elements in the film "Ego". The method used is the method of creation including the creation stage (idea creation), the planning stage (library research and observation methods) and the implementation stage (pre-production, production and post-production). The main theory in this paper uses the editing theory by Mabruri (2013) regarding editing techniques using rhythmic aspects and shaping aspects of editing. The conclusion obtained in this paper is the application of the rhythmic aspect in the film "Ego" is realized by controlling the rhythm of the short shot length with sound, image size, camera movement and subject movement in the film, which is applied to the scene opening taste, 14, 15, 16, 19, 24, 25, 27 and 28. In addition, the rhythmic aspect greatly influences the narrative structure of the story in the film "Ego" through its editing elements, so that the impression of a comedy drama can be conveyed properly to the audience.